The Relationship Between the Score on a Simple Measure of Cognitive Function and Incident CVD in People With Diabetes: A Post Hoc Epidemiological Analysis From the ACCORD-MIND Study - Cukierman-Yaffe, Tali (J Clin Endocrinol Metab, 2017)
CONTEXT AND OBJECTIVE: Diabetes is associated with a greater risk for incident cardiovascular disease and cognitive dysfunction. This study aimed to investigate, in people with type 2 diabetes, the association of a simple measure of cognitive function to cardiovascular disease events and mortality. DESIGN, SETTING, PARTICIPANTS, MEASUREMENTS, AND OUTCOMES: The Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial included persons with longstanding type 2 diabetes. A substudy of 2977 (Memory in Diabetes) participants aged 55 years or older aimed to test the effect of the interventions on brain structure and function. At baseline, participants were administered a cognitive battery that included the digit symbol substitution test (DSST). The associations of the DSST and the ACCORD primary outcome (the first occurrence of nonfatal myocardial infarction or nonfatal stroke or death from cardiovascular causes) and all-cause mortality were investigated with Cox proportional hazard models adjusting for several demographic and clinical variables. RESULTS: Median follow-up time was 4.27 years. An inverse relationship between the incidence of the ACCORD primary outcome and baseline cognitive score was demonstrated. A 1-point higher DSST score was associated with a lower incidence of the primary outcome (hazard ratio, 0.987; 95% confidence interval, 0.977 to 0.998; P = 0.019), after adjustment for demographic and clinical trial factors, additional baseline cardiovascular risk factors, and self-reported need for assistance to follow the protocol. CONCLUSION: Lower scores on the DSST, a simple, sensitive neuropsychological instrument, are associated with a higher incidence of cardiovascular events in persons >55 years old with longstanding diabetes.